2018
DOI: 10.1111/cas.13794
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of kinesin family member 20B sensitizes hepatocellular carcinoma cell to microtubule‐targeting agents by blocking cytokinesis

Abstract: Kinesin family member 20B (KIF20B, also known as MPHOSPH1) is a kinesin protein that plays a critical role in cytokinesis. Previously, we and others have demonstrated the oncogenic role of KIF20B in several cancers; however, the exact mechanisms underlying its tumorigenic effects remain unclear. Herein, we showed overexpression of KIF20B in human hepatocellular carcinoma (HCC) and reported a negative correlation between KIF20B level and prognosis of patients. Mechanistically, reducing KIF20B blockades mitotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 43 publications
4
18
0
Order By: Relevance
“…A recent study suggested to target the KIF20B gene in the treatment for hepatocellular carcinoma (38). Inhibition of KIF20B can block mitosis at both metaphase and telophase, which enhance the cytotoxicity of two chemotherapeutic drugs, hydroxycamptothecin, and mitomycin C (39). The role of KIF20B in tumorigenesis of meningiomas, especially multiple lesions, suggests that its suppression might be a novel strategy in the treatment for multiple meningiomas in the future.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggested to target the KIF20B gene in the treatment for hepatocellular carcinoma (38). Inhibition of KIF20B can block mitosis at both metaphase and telophase, which enhance the cytotoxicity of two chemotherapeutic drugs, hydroxycamptothecin, and mitomycin C (39). The role of KIF20B in tumorigenesis of meningiomas, especially multiple lesions, suggests that its suppression might be a novel strategy in the treatment for multiple meningiomas in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of KIFs might result in a series of errors including excessive spindle separation, premature separation of sister chromatids, advanced leads, and eventually bipolar or unipolar spindles, while lost expression of KIFs might lead to the opposite result (28). Abnormalities in these functions might eventually lead to the development of different diseases, including tumors (310). KIF20A was reported to promote the invasiveness of pancreatic cancer by regulating the transport of insulin like growth-binding protein 3-containing stress granules (2932).…”
Section: Discussionmentioning
confidence: 99%
“…KIF23 could also promote glioma progression and being regulated by transcription factor 4 (37,38). As a member of kinesin-6 family, KIF20B functions as cancer-testis antigen specific to human bladder cancer (4,5), which is associated with cell proliferation and tumor growth in hepatocellular carcinoma through targeting p53, serving a crucial role in cancer (610). However, unlike KIF20A, there are few studies on the function and mechanism of KIF20B in tumors (4,610), especially in tongue cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations